Developing and perfecting universal cognitive skills of students through integrating scientific knowledge about information in the learning content - Tsibizova, Oksana (2021)
The article substantiates the need to integrate the findings of linguistics and information theory for the selection of learning content aimed at developing and perfecting the universal cognitive skills of students of a technical university. Consideration of the concept of information in the learning process, the amount of information, and the quality of information may reveal new insights into the information processes produced by an individual in communication. The authors of the article understand the information process as an action with textual information, leading to its qualitative or formal change with one or another communicative aim.The learning algorithms for working with textual information, proposed by the authors of the article, allow not only to speed up the process of understanding and consolidating the course content but also provide for a self-reflection component of students' activity, which makes it possible to control, correct and modify the algorithm under the influence of changing communication conditions.